2023
DOI: 10.1093/lambio/ovad045
|View full text |Cite
|
Sign up to set email alerts
|

Activity of plant essential oils against clinically and environmentally isolatedSalmonella entericaserotypes:in vitroassays and molecular docking

Abstract: This research aimed to evaluate the antimicrobial activity of essential oils (EOs) against clinically and environmentally-isolated Salmonella serotypes. Oregano, thyme, and grapefruit EO compounds were identified, and the antimicrobial activity was evaluated against the S. Saintpaul, Oranienburg, and Infantis serotypes. In addition, molecular docking was performed to explore the possible mechanisms between compounds of EOs with microbial enzymes. Thymol was the main compound identified in oregano (44.0%) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The thyme essential oil was used as an antiparasitic or to treat minor wounds from ancient times due to its strong antimicrobial properties [21,22]. Lavender [23,24], grapefruit [25,26], bergamot [27,28], cinnamon [29,30], and rosemary [31,32] essential oils have strong antimicrobial activity and therefore are good candidates for innovative antibacterial and antifungal therapies and materials. Nevertheless, the essential oils must be loaded or encapsulated in a matrix, be it organic or inorganic, to ensure a longer release profile, and a sustained antimicrobial activity [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The thyme essential oil was used as an antiparasitic or to treat minor wounds from ancient times due to its strong antimicrobial properties [21,22]. Lavender [23,24], grapefruit [25,26], bergamot [27,28], cinnamon [29,30], and rosemary [31,32] essential oils have strong antimicrobial activity and therefore are good candidates for innovative antibacterial and antifungal therapies and materials. Nevertheless, the essential oils must be loaded or encapsulated in a matrix, be it organic or inorganic, to ensure a longer release profile, and a sustained antimicrobial activity [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the poultry and pig industry, the main reservoirs of Salmonella, feeding strategies aimed at optimizing intestinal functions may have an impact on the colonization of Salmonella in the digestive tract. Among them, we must highlight the acidification of feed by means of organic acids, the use of probiotics, prebiotics, or phytobiotics, and the new lines of research on the incorporation of essential oils (EOs) extracted from plants [107,108]. Most of these products are used in animal health as feed additives, and their approval as therapeutics requires proven scientific studies that demonstrate their antimicrobial efficacy, effect on animal production, and safety for public and environmental health.…”
Section: Feeding Strategiesmentioning
confidence: 99%
“…The efficacy of EOs obtained mainly from oregano, cinnamon, thyme, and citrus fruits have been evaluated against Salmonella serovars [109][110][111]. As an example, the effect of EOs against Salmonella serovars isolated from human outbreaks and river water has recently been investigated [108]. This research showed that oregano best inhibited the growth of clinical and environmental Saintpaul, Oranienburg, and Infantis serovars, followed by thyme and grapefruit EOs.…”
Section: Feeding Strategiesmentioning
confidence: 99%
“…Utilization of clove, peppermint, litsea, lemongrass, and cinnamon essential oils were additionally investigated as an efficacious feed additive in the poultry industry [104]. Most recently, oregano, thyme, and grapefruit essential oils were studied as alternatives to antibiotics in poultry feed [105].…”
Section: Essential Oilsmentioning
confidence: 99%